Wheat Cost-Return Budget in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2001)
This publication projects a budget that reflects expected income and costs based on typical production of wheat in western Kansas.
MF903_2001_10
Keywords: MF909; Economics; Crops; MF